ANALISIS BEBAN KERJA TUGAS POKOK DAN TAMBAHAN TIM MANAJEMEN MUTU DI UPTD PUSKESMAS KAHURIPAN KOTA TASIKMALAYA - 'Aisy, Bilqiis Rihhadatul; Muharry, Andy; Neni, Neni (Jurnal Kesehatan Komunitas Indonesia, 2023)
Less optimal performance is affected by excessive workload. To be able to control the quantity and quality of health services at the Puskesmas, it is necessary to do a workload analysis. The research design used is descriptive-qualitative. The determination of research informants was carried out using a purposive sampling technique. Informants in this study include as many as 10 people. The main tasks of the quality management team are those who serve as junior midwives, health laboratory institutions, first-time general practitioners, supervising nurses, associate dentists, associate nutritionists, environmental sanitationists, and associate general practitioners. Additional duties of the quality management team consist of the person in charge of quality, quality secretary, PPI coordinator, risk management coordinator, patient safety coordinator, K3 coordinator, internal audit coordinator, UKM coordinator, and UKP coordinator. The workload of young specialist midwives, health laboratory personnel, and first specialist general practitioners is included in the excess category. Additional task workload requires employees to carry out quality management tasks with as many as seven people. The suggestion that can be made is to carry out workload analysis related to main and additional tasks so that members who have excessive workload can be identified so that they can redistribute tasks to employees who have less workload. In addition, education and training activities should be carried out so that the implementation of quality management duties is carried out effectively and efficiently.